1992
DOI: 10.1007/bf00372074
|View full text |Cite
|
Sign up to set email alerts
|

The expression of functional MSH receptors on cultured human melanocytes

Abstract: Although alpha-MSH increases skin darkening in humans, there are several reports that it fails to have melanogenic effects on human melanocytes in vitro. The purpose of this study was to see whether cultured human melanocytes express MSH receptors. Human melanocytes were grown in the absence of artificial mitogens such as 12-O-tetradecanoyl phorbol-13-acetate (TPA) and cholera toxin (CT) and incubated for 2 h at room temperature with increasing amounts of 125I-labelled Nle4DPhe7-alpha-MSH with and without exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
87
1
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 15 publications
4
87
1
2
Order By: Relevance
“…The HBL melanoma cell line has previously been demonstrated to express 1000 -3000 MSH receptor-binding sites per cell , and A375 and C8161 melanoma cell lines have also been demonstrated to have MSH receptors (Baumann et al, 1997) and MSH binding sites (Sharma et al, 1996). In comparison, normal human cutaneous melanocytes are reported to express between 300 and 1000 binding sites per cell (Donatien et al, 1992;De Luca et al, 1993). In the present study, MC-1 receptors were identified on the cells by immunofluorescent microscopy, Western blotting and MSH binding sites using radiolabelled a-MSH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HBL melanoma cell line has previously been demonstrated to express 1000 -3000 MSH receptor-binding sites per cell , and A375 and C8161 melanoma cell lines have also been demonstrated to have MSH receptors (Baumann et al, 1997) and MSH binding sites (Sharma et al, 1996). In comparison, normal human cutaneous melanocytes are reported to express between 300 and 1000 binding sites per cell (Donatien et al, 1992;De Luca et al, 1993). In the present study, MC-1 receptors were identified on the cells by immunofluorescent microscopy, Western blotting and MSH binding sites using radiolabelled a-MSH.…”
Section: Discussionmentioning
confidence: 99%
“…Five receptors (MC-1R -MC-5R) have been cloned to date (Mountjoy et al, 1992) and MC-1R is expressed on human keratinocytes, melanocytes and melanoma cells (Donatien et al, 1992;De Luca et al, 1993;Bohm et al, 1999). Loss-of-function polymorphic variants exist (Valverde et al, 1995) and are associated with red-haired individuals who pigment poorly (Schiöth et al, 1999).…”
mentioning
confidence: 99%
“…While in vivo studies clearly demonstrated a hyperpigmentary response in individuals injected with melanotropic hormones (7-10), evidence for a direct effect for melanotropins on normal human melanocytes remained lacking. The recent cloning of the melanocortin receptors, and their expression on normal human melanocytes, has rekindled interest in the biological effects of melanotropins on human melanocytes (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…The cloning of the melanocortin receptors, and subsequent receptor binding studies, verified that human melanocytes express one type of melanotropin receptor, MC1 (14)(15)(16)(17). It was reported that a-MSH, like other cAMP inducers, enhances the proliferation of nevus cells in a dose-dependent manner (18).…”
mentioning
confidence: 98%
“…This receptor has a high basal level of ligand-independent constitutive activity; however the receptor is activated further by its agonist a-melanocyte stimulating hormone (a-MSH) [9][10][11]. a-MSH is a small peptide secreted by the pituitary gland where it is cleaved from the precursor, pro-opiomelanocortin (POMC).…”
Section: Introductionmentioning
confidence: 99%